2015
DOI: 10.1016/j.enggeo.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The development and application of the alteration strength index equation

Abstract: We have developed an alteration strength index (ASI) equation to address the effect of hydrothermal alteration on mechanical rock properties. This equation can be used to estimate a range of rock strengths, comparable to uniaxial compressive strength (UCS), based on rapid analysis of mineralogy and microstructure. We used rock samples from three geothermal fields in the Taupo Volcanic Zone (TVZ) to represent a range of alteration types. These are sedimentary, intrusive and extrusive rocks, typical of geotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In our study, these fluctuations have been attributed to the variations in primary lithological textures and microstructure as well as secondary alteration, dissolution, and re-precipitation. Other studies of burial diagenesis in geothermal systems have observed similar changes in mechanical properties with depth (Tewhey 1977;Stimac et al 2004;Mielke 2009; Dillinger et al 2014;Wyering et al 2014Wyering et al , 2015. This shows that while the primary textures of the deposited lithologies must contribute to the effects of burial diagenesis by reducing porosity and increasing density, the hydrothermal alteration plays a much larger role in controlling the physical properties.…”
Section: Effect Of Increased Depth On Physical Propertiesmentioning
confidence: 55%
“…In our study, these fluctuations have been attributed to the variations in primary lithological textures and microstructure as well as secondary alteration, dissolution, and re-precipitation. Other studies of burial diagenesis in geothermal systems have observed similar changes in mechanical properties with depth (Tewhey 1977;Stimac et al 2004;Mielke 2009; Dillinger et al 2014;Wyering et al 2014Wyering et al , 2015. This shows that while the primary textures of the deposited lithologies must contribute to the effects of burial diagenesis by reducing porosity and increasing density, the hydrothermal alteration plays a much larger role in controlling the physical properties.…”
Section: Effect Of Increased Depth On Physical Propertiesmentioning
confidence: 55%
“…The data presented in this study show that porosity increases as treatment temperature increases (Figure and Table ). Generally, an increase in porosity is associated with a decrease in the strength of hydrothermally altered rock (e.g., Wyering et al, , ; Mordensky et al, ). Weakening intact rock (i.e., rock at the sample scale) will affect the behavior of the intact rock around the wellbore, for example, contributing to changes in drilling performance (as shown in Wyering et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they experience elevated pressures, high temperatures, and corrosive fluids [26,[37][38][39][40]. Such extreme conditions may promote compaction [27,[41][42][43][44], precipitation of secondary mineral phases [26,[45][46][47], and variable degrees of alteration [43,48], modifying the mechanical properties and the permeable-porous network through which fluids circulate. Previous mechanical studies of porous rock compaction [41,49,50] have characterised rock strength by evaluating yield curves to identify the stress conditions where permanent inelastic deformation may occur.…”
Section: Introductionmentioning
confidence: 99%